2009
DOI: 10.1037/a0015550
|View full text |Cite
|
Sign up to set email alerts
|

Brain dynamics in spider-phobic individuals exposed to phobia-relevant and other emotional stimuli.

Abstract: Dense sensor event-related brain potentials were measured in participants with spider phobia and nonfearful controls during viewing of phobia-relevant spider and standard emotional (pleasant, unpleasant, neutral) pictures. Irrespective of the picture content, spider phobia participants responded with larger P1 amplitudes than controls, suggesting increased vigilance in this group. Furthermore, spider phobia participants showed a significantly enlarged early posterior negativity (EPN) and late positive potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
86
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 46 publications
13
86
1
Order By: Relevance
“…N300 has been recognized as a component particularly sensitive to visual stimuli generated by emotional images (Rossignol et al, 2005). With regard to the latency of the N300, subjects with anxiety, fears or phobias showed faster reaction time than control group subjects in the experiments performed by Flykt and Caldara (2006) and Michalowski et al (2009). In our study, EG subjects, who also had higher levels of anxiety compared to CG subjects, showed faster reaction times (shorter latencies) in channels C3 and O2.…”
Section: Discussionsupporting
confidence: 46%
“…N300 has been recognized as a component particularly sensitive to visual stimuli generated by emotional images (Rossignol et al, 2005). With regard to the latency of the N300, subjects with anxiety, fears or phobias showed faster reaction time than control group subjects in the experiments performed by Flykt and Caldara (2006) and Michalowski et al (2009). In our study, EG subjects, who also had higher levels of anxiety compared to CG subjects, showed faster reaction times (shorter latencies) in channels C3 and O2.…”
Section: Discussionsupporting
confidence: 46%
“…Moreover, phobic fear has been shown to modulate processes of stimulus perception and evaluation. For example, we recently reported (Michalowski et al, 2009) that spider phobia participants responded with overall larger P1 amplitudes than controls in a context in which phobia-relevant stimuli are likely to occur, an effect that suggests increased vigilance in this group. Moreover, in our study spider phobia participants exhibited a significantly enlarged early posterior negativity (EPN) during viewing of their feared material than controls.…”
Section: Introductionmentioning
confidence: 95%
“…Circa-strike defense, characterized by strong autonomic arousal and escape behavior, is activated when the threat is imminent. In a recent experiment, we tested this model by measuring electrical brain responses during the presentation of spider pictures to individuals with spider phobia and control participants (Michalowski et al, 2009). The main results of this study together with a sketch of the model can be seen in Figure 1.…”
Section: Etiology: Understanding Specific Phobias From a Neurosciencementioning
confidence: 95%